2023
DOI: 10.1021/acsaem.2c03033
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing of Thylakoid-PEDOT:PSS Composite Electrode for Bio-Photoelectrochemical Cells

Abstract: Thylakoid membranes (TMs) isolated from plant cells produce high-energy electrons by splitting water molecules using solar energy during photosynthesis. Since those photosynthetic electrons (PEs) can be harvested by oxidizing TMs, various approaches to attach TMs on electrodes have been investigated so far. Here, we propose embedding of TMs in the electrically conductive polymeric structure using 3D printing. A photosynthetic and electrically conductive ink based on a mixture ink of TMs and poly(3,4-ethylenedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
(62 reference statements)
1
7
0
Order By: Relevance
“…70–78 Regarding the PE current density of this system, the highest PE current density among recent studies was achieved in this work as shown in Fig. S7 † 10–14,29–33,79–84.…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…70–78 Regarding the PE current density of this system, the highest PE current density among recent studies was achieved in this work as shown in Fig. S7 † 10–14,29–33,79–84.…”
Section: Discussionsupporting
confidence: 51%
“…S7. † [10][11][12][13][14][29][30][31][32][33][79][80][81][82][83][84] For efficient collection of PEs from TMs, TMs need to be attached and electrically connected to a 3D printed graphene electrode. However, since TMs have abundant ionized side groups, they do not form stable bonds with graphene electrodes that are hydrophobic.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations